UNIFICATION OF INFORMATION TECHNOLOGY TERMINOLOGY IN POLISH LAW – SELECTED ISSUES - RADONIEWICZ, Filip (Comparative Legilinguistics, 2012)
In the present article the question of systematisation of information technology terminology in Polish Law is presented. The instrument, which is used for this purpose is the Amendment to Statutes in Order to Unify Information technology terminology Act of the 4th of September 2008. With this Act the number of provisions was amended and uniform terms of information origin were introduced – as an “information data carrier”, an “electronic document”, a “data communications system” and “electronic communications means”. However, these concepts are not defined in the Act but referred to the Implementation of IT Solutions to Entities Executing Public Assignments Activity Act of the 17th of February 2005. The article is divided into three parts. After the short preface in order to introduce the issues discussed, in the main part the author addressed the question of the above mentioned Amendment to Statutes in Order to Unify Information technology terminology Act. The summary is an attempt to make an assessment of regulation in force.